The World Health Organization Classification of dontogenic Lesions: A Summary of the Changes of the 2017 (4th) Edition - Merva SOLUK-TEKKEŞİN; John M. WRIGHT (Federation of Turkish Pathology Societies, 2018)
The 4th edition of the World Health Organization (WHO) Classification of Head and Neck Tumors was published in January 2017. The edition serves to provide an updated classification scheme, and extended genetic and molecular data that are useful as diagnostic tools for the lesions of the head and neck region. This review focuses on the most current update of odontogenic cysts and tumors based on the 2017 WHO edition. The updated classification has some important differences from the 3rd edition (2005), including a new classification of odontogenic cysts, 'reclassified' odontogenic tumors, and some new entities.